Internationalization of the higher education. An introductory exploration about its presence in the posgraduate programs of the University of Costa Rica - Muñoz Varela, Luis (2016)
This article aims to show the results of a research about the information provided in postgraduate programs and study plans at the University of Costa Rica (UCR), related to various academic and management actions performed dealing with the internationalization process of higher education. The research was done by reviewing the information on Web pages and included considering aspects such as: a) inclusion of content in the curricula related to internationalization; b) availability of own Web pages; c) dissemination of the research work under study; d) partnerships with universities, investigation institutes, cooperation agencies and international organizations; e) mastery of a second language as a requirement for admission to programs and plans. It concludes that, to date, internationalization does not seem to have had a greater significance in the activities of management and information disclosure conducting programs and postgraduate courses at UCR.